Auger recombination and carrier transport effects in III-nitride quantum well light emitting diodes - Deppner, Marcus; Roemer, Friedhard; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
Gallium nitride based light emitting diodes (LEDs) have established as powerful devices, that are well suited for general lighting. Despite the progress within the recent years the so-called "efficiency droop" is still a central issue of nitride-based LED research. Up to now, no widely accepted explanation is available for the reduction of the internal quantum efficiency with increasing injection current. We report on a novel mechanism contributing to efficiency droop, that combines two of the previously reported effects: Auger recombination and carrier leakage. A sophisticated Auger model, that takes account of the overlap of the wave functions, is extended to model the energy transfer towards the third involved carrier. This carrier is assumed to be expelled from the well and regenerated in the continuum carrier population, where it can contribute to carrier leakage. A physics-based simulation of a quantum well LED employing a semi-classical approach has been carried out to demonstrate the impact of this effect. Depending on the parametrization, the inclusion of Auger expulsion reduces the Auger coefficient up to 50% when compared to a standard Auger model, which could explain the discrepancy between calculated and experimentally extracted Auger coefficients. © 2013 Copyright SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Auger; compound semiconductors; computational modeling; droop; GaN; InGaN; leakage; LEDs; physics-based simulation; solid-state lighting